Frequency of Painful Benign Tumors of the Hand in Patients presenting to the Hand and Upper Limb Surgery Combined Military Hospital Lahore. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the frequency of painful benign soft tissue and bony tumors of the hand in patients presenting to the Hand And Upper Limb Surgery (HULS) Combined Military Hospital Lahore.Methods: This descriptive study was conducted in the department of Hand and Upper Limb Surgery (HULS) Combined Military Hospital Lahore from 27th May 2017 to 27th May 2022.All adults patients of both gender with pain and or swelling of fingers and palm and fulfilling the inclusion criteria were investigated for soft tissue and osseous tumors. The receiver operative characteristics (ROV) curve was used to look at continuous factors like age and tumor size. Fisher's exact test was used to determine the likelihood of malignancy.Results: The total number of patients with benign tumors of the hand were 49. Male patients were 29(59.1% ) and females were 20(40.8%). The mean age was 39±3.1 years. Soft tissue tumors were diagnosed in 30 (61.2%) patients and bone tumors in 19 (38.7%) patients. Glomus tumor was the most common soft tissue detected in 12 (40%) patients. Enchondroma was the most common bone tumor noted in 9 (56.2%) patients. Majority (46.6%, n=14) soft tissue tumors predominantly involved palm of the hand while bony tumors were located on phalanges in 16(84%,) patients.Conclusion: The frequency of painful benign soft tissue tumors of the hand were more than bony tumors. Soft tissue tumors were located on palms and bony tumors on phalanges in majority of our patients.